DYNAMIC SYSTEM MODEL OF RICE SELF SUFFICIENCY TOWARDS FOOD SECURITY - Trista Fristovana; Musa Hubeis; Eko Ruddy Cahyadi (Jurnal Manajemen & Agribisnis, 2019)
Food security is the condition of fulfilling individual food that is sufficient, safe, equitable and affordable. The main target of fulfilling food sufficiency is dominated by rice self-sufficiency. Rice self-sufficiency is important because it has special reasons in terms of politics and social economy. The sustainability of rice self-sufficiency faces many challenges because domestic rice supply growth is not as fast as rice use. The purpose of this study is to simulate the scenario of achieving self-sufficiency in rice and formulating policy recommendations for developing management to achieve self-sufficiency in rice. Research data includes primary and secondary data. This research uses a dynamic system approach. Simulations carried out from 2018-2045. The simulated policy is intensification, extensification, suppression of postharvest losses and Indonesia a self-sufficiency country as well as an exporter of rice (scenario five), but the policy requires a very large budget. Scenario six, a combination of intensification, suppression of postharvest losses and land conversion becomes an alternative operational policy and is most likely to be applied. Land conversion is the biggest determinant in rice self-sufficiency. Recommendations address for the government include: (1) establish and protect longterm rice fields, (2) identify and map of areas that have the potential for the development of a periodic expansion of food crops; (3) guarantee the availability of agricultural facilities and infrastructure in accordance with the selected policy, both in the form of the application of scenario six and scenario five. Keywords: dynamic system, food security, policy, rice, self-sufficiency